Dimensions of national ethos among educated youths in Malaysia - Ismail, Mohd Mahadee; Hassan, Nor Azlili; Abdullah, Azlina; Mak Din, Hairol Anuar; Md Yunus, Marzudi; Mohd Noor, Mansor (Universiti Putra Malaysia, 2021)
This article focuses on dimensions of national ethos among educated youths in Malaysia by developing a confirmatory factor analysis (CFA) model. The main objective is to evaluate national ethos dimensions and develop a CFA model of the national ethos formation. These objectives are achieved by applying four main dimensions to confirm the formation of national ethos: values, feelings and spirit, beliefs and identity dimensions. The study was conducted using a quantitative approach through survey techniques involving 431 students of Universiti Putra Malaysia, comprising 241 Malay and 190 Chinese youth groups. The data analysis used the SEM-AMOS approach to develop a CFA model of the national ethos. The results confirm national ethos of educated youth is formed through the four main dimensions measured. The CFA model has achieved a good level of compatibility based on the set indicators (CMIN = 600.947, DF = 115, CMIN / DF = 5.226, p = 0.000, SRMR = 0.0937, RMSEA = 0.099, CFI = 0.927 and PNFI = 0.771). This study implies a CFA model as a new approach in national ethos formation among educated youths in Malaysia. A future evaluation of a non-educated youth group should also be implemented to assure that this model becomes a holistic model.